Alterations in Saliva and Plasma Cytokine Concentrations During Long-Duration Spaceflight - Krieger, Stephanie S.; Zwart, Sara R.; Mehta, Satish; Wu, Honglu; Simpson, Richard J.; Smith, Scott M.; Crucian, Brian (Frontiers in Immunology, 2021)
Long-duration spaceflight is known to cause immune dysregulation in astronauts. Biomarkers of immune system function are needed to determine both the need for and effectiveness of potential immune countermeasures for astronauts. Whereas plasma cytokine concentrations are a well-established biomarker of immune status, salivary cytokine concentrations are emerging as a sensitive indicator of stress and inflammation. For this study, to aid in characterizing immune dysregulation during spaceflight, plasma and saliva cytokines were monitored in astronauts before, during and after long-duration spaceflight onboard the International Space Station. Blood was collected from 13 astronauts at 3 timepoints before, 5 timepoints during and 3 timepoints after spaceflight. Saliva was collected from 6 astronauts at 2 timepoints before spaceflight, 2 timepoints during and 3 timepoints following spaceflight. Samples were analyzed using multiplex array technology. Significant increases in the plasma concentration of IL-3, IL-15, IL-12p40, IFN-α2, and IL-7 were observed during spaceflight compared to before flight baseline. Significant decreases in saliva GM-CSF, IL-12p70, IL-10 and IL-13 were also observed during spaceflight as compared to compared to before flight baseline concentrations. Additionally, plasma TGFβ1 and TGFβ2 concentrations tended to be consistently higher during spaceflight, although these did not reach statistical significance. Overall, the findings confirm an in-vivo hormonal dysregulation of immunity, appearing pro-inflammatory and Th1 in nature, persists during long-duration orbital spaceflight. These biomarkers may therefore have utility for monitoring the effectiveness of biomedical countermeasures for astronauts, with potential application in terrestrial research and medicine.